2019
DOI: 10.1186/s12891-019-2786-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between multifidus fatty atrophy and lumbar disc degeneration in low back pain

Abstract: Background Chronic low back pain (LBP) is common and associated with lumbar disc herniation. The purpose of this study was to investigate if the grade of lumbar disc degeneration correlates with the degree of lumbar multifidus muscle (LMM) fatty atrophy. Methods A retrospective analysis on 16 males and 19 females with chronic LBP and a mean age of 47.2 years. Using MRI, the grade of lumbar intervertebral discs degeneration was assessed according to the Pfirrmann classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
85
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 22 publications
10
85
0
6
Order By: Relevance
“…Certain studies have reported that the degree of fatty infiltration of multifidus muscle at the same level as the ipsilateral segment of the LDH was significantly higher than on the contralateral segment. These findings confirmed the feasibility and reliability of visually evaluating the degree of fatty infiltration of multifidus muscle [ 6 , 14 , 17 , 26 ]. Additionally, it was also reported that compared to assessing the cross-sectional area in patients with lumbar disc herniation, it was much more effective to assess the degree of multifidus fatty infiltration [ 27 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Certain studies have reported that the degree of fatty infiltration of multifidus muscle at the same level as the ipsilateral segment of the LDH was significantly higher than on the contralateral segment. These findings confirmed the feasibility and reliability of visually evaluating the degree of fatty infiltration of multifidus muscle [ 6 , 14 , 17 , 26 ]. Additionally, it was also reported that compared to assessing the cross-sectional area in patients with lumbar disc herniation, it was much more effective to assess the degree of multifidus fatty infiltration [ 27 ].…”
Section: Discussionsupporting
confidence: 72%
“…Faur et al reported that multifidus muscle degeneration primarily occurred along the cross-section of MRI scans. Additionally, they reported that the degree of multifidus muscles degeneration was proportional to the degree of disc degeneration [ 26 ]. In this study, the patients with ULDH are significantly different from healthy people in the measurement indexes of the multifidus muscles.…”
Section: Discussionmentioning
confidence: 99%
“…farklı seviyelerdeki disk dejenerasyonlu hastalarda en fazla atrofinin L5-S1 seviyesi lomber multifidus kasında olduğunu göstermişlerdir. 29 Biz de bu çalışmada L5-S1 seviye lomber disk hernisi tanılı akut bel ağrılı hastalarda lomber multifidus kasının kesit alanı bilateral olarak inceledik. Farklı çalışmalarda multifidus kesit alanları unilateral olarak hesaplanmasına karşın çalışma grubumuzdaki hastaların akut evre olması ve yaygın bel ağrısı tanımlaması sebebiyle MRG hesaplamaları, bilateral ölçüm toplamı alınarak yapıldı.…”
Section: Discussionunclassified
“…çalışmalarında kronik evrede farklı seviyedeki disk dejenerasyonlarıyla lomber multifidus kas atrofisi arasında düşük bir ilişki olduğunu da göstermişlerdir. 29 Ancak çalışmamızdan farklı olarak bu çalışma kronik evredeki bulging, protrüzyon, ekstrüzyon ve sekestrasyon evre disk hernili hastalar üzerinde yapılmış ve en büyük atrofi, kronik ve ilerlemiş disk hernilerinde bulunmuştur. Boyacı ve ark.…”
Section: Discussionunclassified
“…ise LMK ile lomber disk dejenarasyonu arasındaki ilişki olduğunu göstermişlerdir. LMK atrofisinin alt lomber bölgede daha yüksek olduğunu ve dejenerasyon arttıkça atrofininde de arttığını gözlemlemişlerdir(22). Başka bir çalışmada her ne kadar klinik sonuçları bilinmese de, postoperatif 1. gündeki CK seviyelerinin MED ve açık diskektomi arasında kıyasladığında, MED grubunda kas atrofisi sonuçlarının daha iyi olduğu gözlenmiştir(30).…”
unclassified